Sinyal Going Concern Emiten Pertambangan: Keahlian Komite Audit, Kepemilikan Institusional, dan Risiko Litigasi - Denny Putri Hapsari; Santi Octaviani (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2026)
This study examines the effect of audit committee expertise, institutional ownership, and litigation risk on the receipt of going concern audit opinions among mining companies listed on the Indonesia Stock Exchange during 2020-2024. Going concern opinion is an important audit signal because it communicates material uncertainty regarding an entity's ability to continue operating and may influence investors, creditors, and regulators. The study applies a quantitative explanatory approach using secondary data obtained from audited financial statements, annual reports, and independent auditor reports. The sample consists of 44 mining companies selected through purposive sampling, resulting in 220 firm-year observations. Logistic regression is employed because the dependent variable is dichotomous. The results show that audit committee expertise has a positive and significant effect on going concern opinion acceptance, while institutional ownership has a negative and significant effect. Litigation risk does not significantly affect the auditor's decision. These findings indicate that governance quality and ownership monitoring are more salient than litigation exposure in explaining going concern audit reporting in the Indonesian mining sector.